Statistical Study of the Internal Water – Conceptions, Definitions, Indicators and Estimations - Pavlova, Veselka (Research Papers, 2010)
Source of data are the annual statistical surveys on water, which include the following surveys: Survey on services related to water supply, sewage and waste water purification – exhaustive, Survey on water use.Water quantities are recorded through direct methods of measurement, and in absence of such the estimate is accomplished by the way of calculation – based on the specific technological processes, capacity of the water abstraction/treatment equipment, etc.Basic indicators, definitions discussed in the study are: fresh water; non-fresh water, gross water abstraction; returned water, water net abstraction – self-supply, public water supply, other water supply; water used, cooling water, water losses; waste water – waste water generated from point sources, waste water collected into the public sewerage, urban waste water treatment; primary treatment, secondary treatment, tertiary treatment, waste water discharged into water bodies, population (average annual), connected to public water supply/public sewerage, population (average annual) with independent waste water treatment, etc.The use of water resources and preventing them from pollutants is not only an ecological question, but essential factor for sustainable economic growth especially under conditions of water scarcity and more and more frequent droughts.